2019
DOI: 10.1101/621854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transient Receptor Potential Ankyrin1 channel is endogenously expressed in T cells and regulates immune functions

Abstract: Transient Receptor Potential channel subfamily A member 1 (TRPA1) is a non selective cationic channel, identified initially as a cold sensory receptor. TRPA1 responds to diverse exogenous and endogenous stimuli associated with pain and inflammation. However, the role of TRPA1 towards T cell responses remains scanty. In this work, we explored the endogenous expression of TRPA1 in T cells. By RT-PCR we confirmed the expression of TRPA1 in T cell at RNA level. Using confocal microscopy as well as flow cytometry, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Besides regulating intracellular Ca 2+ levels, few TRP channels belonging to the vanilloid (TRPV), melastatin (TRPM), and ankyrin (TRPA1) are also thermosensitive in nature (Baez‐Nieto et al, 2011). Recently, we have shown that heat sensitive TRPA1 channel is functionally present in CD3 + T cells and influences T‐cell activation (Sahoo et al, 2019). We have also shown that the thermosensitive TRPV channels (TRPV1, TRPV2, TRPV3, and TRPV4) are functionally expressed in primary murine and human T cells (Majhi, Sahoo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Besides regulating intracellular Ca 2+ levels, few TRP channels belonging to the vanilloid (TRPV), melastatin (TRPM), and ankyrin (TRPA1) are also thermosensitive in nature (Baez‐Nieto et al, 2011). Recently, we have shown that heat sensitive TRPA1 channel is functionally present in CD3 + T cells and influences T‐cell activation (Sahoo et al, 2019). We have also shown that the thermosensitive TRPV channels (TRPV1, TRPV2, TRPV3, and TRPV4) are functionally expressed in primary murine and human T cells (Majhi, Sahoo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%